Managerial Psychology and its Impact on Job Satisfaction among Public Healthcare Employees in Sindh - Qureshi, Saleem Raza; Larik, Abdul Razaque; Mahar, Qamaruddin (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To determine the influence of managerial psychology on healthcare workers drawing from the construct of managerial psychology. METHODOLOGY: A quantitative research approach based on survey design was used. The data was gathered from respondents between February - November 2020 who were chosen randomly from five tertiary-level hospitals in Sindh and 37 rural health centres. Data analysis was analyzed using SPSS Version 22 and AMOS version 22. Employing the psychological capital (PsyCap) scale and Deci and Ryan’s self-determination questionnaire, this study gathered data from 385 public sector employees working in the healthcare sector, examining the association between the study variables. The inclusion criteria comprised participants who were employees in both clinical and non-clinical capacities, male and female, working in 5 designated public sector hospitals or 37 Rural Health Centres in Sindh province. RESULTS: The findings demonstrate a favourable association between optimism and job autonomy. Hope had a significant impact on healthcare employees" job autonomy. CONCLUSION: The findings highlight a correlation between psychological capital and job autonomy. KEYWORDS: Psychological capital; job autonomy; managerial psychology, self-efficacy, hope, optimism, resilience